2009
DOI: 10.1117/12.810993
|View full text |Cite
|
Sign up to set email alerts
|

Is Grannum grading of the placenta reproducible?

Abstract: Publication information7263 : W1-W6 ABSTRACTCurrent ultrasound assessment of placental calcification relies on Grannum grading. The aim of this study was to assess if this method is reproducible by measuring inter-and intra-observer variation in grading placental images, under strictly controlled viewing conditions. Thirty placental images were acquired and digitally saved. Five experienced sonographers independently graded the images on two separate occasions. In order to eliminate any technological factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Perhaps this is due to the subjectivity of this method as while intra‐observer agreement in grading placentas is generally good, agreement between observers has been only fair for all Grannum grades and poor for grade III 35. A more recent study, performed under strictly controlled viewing conditions, confirmed the lack of reproducibility associated with Grannum grading 36…”
Section: Placental Lesionsmentioning
confidence: 99%
“…Perhaps this is due to the subjectivity of this method as while intra‐observer agreement in grading placentas is generally good, agreement between observers has been only fair for all Grannum grades and poor for grade III 35. A more recent study, performed under strictly controlled viewing conditions, confirmed the lack of reproducibility associated with Grannum grading 36…”
Section: Placental Lesionsmentioning
confidence: 99%